The geopolitics of connectivity, cooperation, and hegemonic competition: The Belt and Road Initiative. Issue 99 (February 2019) - Flint, Colin; Zhu, Cuiping
Abstract: China's Belt and Road Initiative (BRI) has been interpreted as a strategy of economic development using new infrastructure projects to intensify regional and global trade relations. It has also been interpreted as a means for China to increase its influence in East and Southeast Asia, with implications for geopolitical competition with the United States. Using a political economy approach that identifies territorial and economic logics of power as integrated in a single logic, we argue that the economic and political processes and goals of the BRI are inseparable. We build upon the strategic coupling and Global Production Networks literature to show that the territorial arrangements of GPNs have local, regional, and global implications. We conclude that the BRI is not either an economic or political project, but one that transforms politics at multiple scales and has the potential to be transformative and will simultaneously create possibilities for global cooperation and conflict.